Echo Character and Sedimentary Processes on the Continental Shelf of the São Paulo State - Araujo, Ligia Dias de (2018)
Sedimentary processes are critical geological phenomena in the evolution of continental margins. Environmental forces from various temporal and spatial scales control these processes. Due to the fast increase of anthropogenic activities in marine environments, these studies on sedimentary processes and their products are becoming increasingly necessary. In this context, geophysical data, such as high-resolution 2D seismic reflection profiles, are efficient tools to characterize sedimentary processes and deposits. This study aimed to map and interpret different types of echo character on the continental shelf of the São Paulo Bight to increase the knowledge of the spatial variability of sedimentary processes in current-dominated shelf settings. With this aim, 120 seismic lines, almost 3200 km in length, have been analyzed in conjunction with 451 surficial sediment samples. Based on the broad-scale seafloor morphology, microtopography and seismic characteristics (e.g., sharpness, amplitude, continuity) of sub-bottom reflections, seven echo types distributed in three echo classes were identified in the study area. Type 1-1 is a flat seafloor with either no or low-amplitude sub-bottom reflectors, mainly observed in the middle shelf; type 1-2 is a flat sea floor with medium to high-amplitude sub-bottom reflectors also found in middle shelf settings; type 1-3 is defined by a transparent acoustic response below the seafloor evolving downsection into a highly reflective pattern that covers most of the inner shelf; type 1-4 presents a flat seafloor molded by regularly spaced undulations, and it is restricted to the outer shelf; type 2-1 consists of mounds with no internal reflectors also located on the outer shelf; type 3-1 is an irregular echo with prolonged internal reflectors found around the São Sebastião Island; finally, type 3-2 is a broad irregular echo with high relief variations mainly found in the outer shelf. The analysis of the seismic survey allowed recognizing that the distribution of the echoes reflects not only the composition of the seabed but also the sedimentary processes that acted during the deposition of the material. In the inner shelf and middle shelves, the Brazilian Coastal Current and the action of waves are the main processes responsible for the echo types found, while the outer shelf echo types are strongly influenced by the Brazil Current.